Rogue Knight - Mull, Brandon, 1974- (Mull, Brandon, 1974- Five Kingdoms, 2014)
When the hunt for his lost friends leads Cole Randolph to the kingdom of Elloweer, he and new friends Mira, Twitch, and Jace team up with the resistance movement to search for Mira's sister, Honor, but enemies abound and Cole and Mira must use a new kind of magic to protect themselves.